2021
DOI: 10.1021/acs.est.1c01812
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Trophodynamics of Marine Lipophilic Phycotoxins in a Subtropical Marine Food Web

Abstract: Marine lipophilic phycotoxins (MLPs) are produced by toxigenic microalgae and cause foodborne illnesses. However, there is little information on the trophic transfer potential of MLPs in marine food webs. In this study, various food web components including 17 species of mollusks, crustaceans, and fishes were collected for an analysis of 17 representative MLPs, including azaspiracids (AZAs), brevetoxins (BTXs), gymnodimine (GYM), spirolides (SPXs), okadaic acid (OA), dinophysistoxins (DTXs), pectenotoxins (PTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The correlation results strongly suggest that using fish body size or trophic position as a threshold to indicate the associated risk and prevent human consumption of contaminated fish is not a practical approach for policymakers to manage risks associated with MLPs. Many studies have reported no or weak correlations between MLPs or an individual MLP, and body size, trophic level, or lipid content in studied fish of Hong Kong, Hawaii, Kiribati, the Caribbean, Okinawa, and French Polynesia. ,, These results indicated that the accumulation of MLPs may involve a mixture of factors beyond the body size, lipid content, and trophic level. Abiotic factors (e.g., temperature, current, and turbidity) and other biotic factors (e.g., age, feeding preference, and the ability for toxin uptake and depuration) may influence MLP accumulation. ,, However, several studies have found strong correlations between body size or lipid content and toxin levels in certain species.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The correlation results strongly suggest that using fish body size or trophic position as a threshold to indicate the associated risk and prevent human consumption of contaminated fish is not a practical approach for policymakers to manage risks associated with MLPs. Many studies have reported no or weak correlations between MLPs or an individual MLP, and body size, trophic level, or lipid content in studied fish of Hong Kong, Hawaii, Kiribati, the Caribbean, Okinawa, and French Polynesia. ,, These results indicated that the accumulation of MLPs may involve a mixture of factors beyond the body size, lipid content, and trophic level. Abiotic factors (e.g., temperature, current, and turbidity) and other biotic factors (e.g., age, feeding preference, and the ability for toxin uptake and depuration) may influence MLP accumulation. ,, However, several studies have found strong correlations between body size or lipid content and toxin levels in certain species.…”
Section: Discussionmentioning
confidence: 96%
“…Moray eels are more likely to accumulate MLPs due to their top predator position in the food chain and low elimination efficiency (a half-life of over 264 days for CTXs). , They have been considered high-risk species for ciguatera food poisoning in Kiribati, Japan, Vietnam, Canary Islands, and New Caledonia. ,, Snapper and grouper are also sedentary and high-order carnivores, with epibenthic behavior and strong site fidelity . It was reported that most MLPs tend to accumulate in benthic communities, which is consistent with our study of high MLP levels in snapper and grouper . Soldierfish Myripristis berndti and Myripristis hexagona, which mainly feed on plankton, such as crab larvae, have detected certain levels of MLPs (Table S5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations